Énergétique et régulation de la fonction de reproduction chez des femelles captives Babouins Olive (Papio anubis) - Cécile Garcia (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The aim of this study was to assess energetic and social parameters of lactating female baboons, and to test the possible role of these factors on different reproductive variables such as postpartum amenorrhea duration or interbirth intervals. A 2-year follow-up was carried out for a sample of 23 multiparous and semi-free living lactating female baboons. There were no rank-related differences in mean energy intakes among the females. All females were in good physical condition and had positive energy balance. The energy costs of lactation were primarily covered by 2 behavioural adaptations: moderate energy intakes increase, particularly during the second and third quarter of lactation, and physical activity decreases. Compared with free-living female baboons, reduced energetic constraints (adequate energy intakes and moderate energetic expenditure) explain short postpartum amenorrhea durations and interbirth intervals in our sample. Fertility is strongly influenced by dominance rank, low-ranking females having longer delays before conception and longer inter-birth intervals. Moreover, mothers with heavier infants have shorter postpartum amenorrhea durations and need fewer cycles to conceive. High-ranking females or those in good physical condition appear likely to withstand relatively rapid infant growth which is independent of the infant’s sex, and have therefore higher reproductive rates. It is unlikely that nutritional mechanisms alone affect the relationship between dominance status and fertility, and our results suggest rather that social stress would also interfere with regulation of reproductive function.